Emotional Dimensions of Infidelity: An Analysis of Psychological and Emotional Factors Affecting Relationship Infidelity (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2023)
This study examines the psychological and emotional aspects that influence romantic infidelity. The study uses quantitative surveys and qualitative interviews to understand emotional infidelity and its effects on relationships. Emotional intimacy shapes people's reactions to emotional infidelity, according to study. Attachment theory shows how attachment styles affect people's willingness to form emotional bonds outside of committed relationships. Unmet emotional wants and fears prompt anxious attachment styles to seek emotional connections outside their partnerships. The study emphasizes relationship communication patterns. Open discourse, emotional sharing, and mutual understanding can avoid emotional infidelity, which is linked to poor communication. The study examines how internet interactions affect emotional infidelity. The findings highlight how easily emotional ties may grow on digital platforms, raising questions about the limits between online interactions and emotional closeness in committed relationships. This research affects relationship treatment and education. Communication skills, attachment insecurities, and emotional intimacy interventions can avoid emotional infidelity. Couples can create trust and contentment through nurturing emotional connections in the primary relationship. This study illuminates emotional infidelity's psychological and emotional aspects. This study examines attachment styles, communication patterns, and the digital age to inform future research, interventions, and methods for better relationships. In a changing world, emotional infidelity must be addressed to build lasting partnerships.